Evaluasi Kebijakan Pemerintah Daerah dalam Pembinaan Prestasi Olahraga - Dian Estu Prasetyo; Damrah Damrah; Marjohan Marjohan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this research is to know the evaluation of local government policy in coaching sport achievement in Tebo District. The results of the study as follows 1 Government policy in sports development achievement in Tebo Regency is not relevant to the needs of pengcab and athletes, 2 Government policy in the provision of sports facilities and infrastructure achievement in Tebo regency not yet relevant to the needs of pengcab and athlete, 3 Government policy in management of achievement sports organization in Tebo District is not yet relevant to the needs of pengcab and athletes, 4 Government policy in budgeting of coaching is not yet relevant to the needs of sports and athletes, 5 Government policy in awarding is not yet relevant to thewishes of shabbersand athletes. Keywords: Government Policy, Development of Sport Achievement